The possible implementations of CLIL, content and language integrated learning, in Slovene and Scottish primary schools from a teacher's point of view - Ule, Katarina (Vestnik za tuje jezike, 2012)
The following article summarizes the main characteristics of CLIL methodology in order to determine the possible implementations of CLIL in Slovene and Scottish primary schools from the teacher's point of view. This method has a dual focus on the content as well as on language learning. The provision of CLIL is to an extent similar in both countries, in Slovenia as well as in Scotland, although their relationship to modern language learning is differently conditioned, since English is the most widely used international language. To better understand the potential implementation of CLIL in Slovene and Scottish primary education, part of it is also devoted to the national curricula for modern language learning, current in both countries. Finally, the results obtained by a survey made among Slovene and Scottish primary school teachers are presented on the subject of their relationship towards CLIL.
Keywords: tuji jeziki; Slovenia; Slovenija; Škotska; osnovne šole; medpredmetno povezovanje; integriran pouk; jezikovni pouk